Fostering A School Culture That Is Resilient To Bullying Through Character Building by Islamic Education Teachers - Khasanah, Elisatun; Saefudin, Ahmad (ANDRAGOGI, 2025)
The high prevalence of bullying in Indonesian schools indicates the urgency to take more serious action in addressing this issue. Bullying has a very damaging impact on students' psychological, emotional, and academic development. The study aims to describe and analyze the role of Islamic Religious Education teachers in building a school culture free from bullying through the implementation of character education based on Islamic teachings. The research method used is a qualitative approach with a literature study method. Data collection techniques were carried out by searching documents (library documentation). Data analysis was done using reduction, presentation, and conclusion drawing. This research shows that a bullying-free school culture is highly dependent on character education that is consistently instilled. PAI teachers have a strategic role in shaping students' character through teaching Islamic values such as compassion, justice, and mutual respect. These values are not only taught theoretically, but also realized through exemplary, experiential learning and collaborative activities such as discussion, role-play, and group learning. PAI teachers not only act as educators but also as drivers of change who are able to create a positive school culture that is free from bullying behavior.